The Effect of Cubing Technique in Teaching Report Text Writing - Rahayu, Yayu Sri; Kusnandar, Agus (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This article investigates the impact of employing the Cubing Strategy in the first semester students of the English Language Education Study Program while teaching writing, specifically report texts. According to the authors' teaching experience, many students struggle with creating report texts. They have difficulty on how to compose report text. In light of this issue, the lecturer must employ an engaging technique in the teaching and learning process to help students comprehend how to create the text. Cubing technique is a creative, hands-on practice that fosters critical thinking, promotes a greater grasp of a topic, and encourages in-depth investigation of it. It employs a cube-shaped visual organizer to encourage students to examine a topic from multiple perspectives. On each face of a cube, the learner writes responses to questions or suggestions. Applying the Cubing Strategy to the production of a report text can aid students in gaining a deeper grasp of the issue through the use of six viewpoints that are pertinent to the subject, enabling them to produce a quality report text. This mixed-methods study involving 48 first-semester English language Education students examined the use of the cubing strategy to the acquisition of report writing. The purpose of this study was to investigate the impact of the cubing technique on students' report writing skill and their perceptions of its implementation. The statistical evidence indicated a significant difference in the students' writing scores on the students' report text writing pre-test (M=48.75) and post-test (M=70.93, the alternative hypothesis (Ha) was accepted because the p-value was less than 0.05, which encapsulates that the students' report text writing was improved. The qualitative findings also revealed students' perspectives of the adoption of the cubing technique, it was discovered that the technique improved students' writing skills, learning motivations, and language development for a variety of skills, such as reading and vocabulary enhancement. Future research implications and suggestions are discussed. Keywords: Cubing Technique, Report Text, Writing